HYPERPLASTIC CANDIDIASIS IN HEPATOCELLULAR CARCINOMA: CASE REPORT - Hidayah, Riski Amalia; Prihanda, Atha; Miniarny, Elisa Astuty (Fakultas Kedokteran Universitas Jenderal Soedirman, 2023)
Background: Hepatocyte-derived tumors include hepatocellular carcinoma (HCC). HCC is the sixth occurrence to occur globally in 2018. When the patient's prognosis is poor, HCC is diagnosed. Due to HCC's impact on the patient's immunity, diseases like candidiasis are more likely to strike. Case Study At RSUD Prof. Dr. Margono Soekardjo, a 66-year-old male patient complained of a white coating around his tongue. The patient's skin and sclera appeared yellow during extraoral examination. A full blood count revealed high levels of leukocytes, RDW, and monocytes but low levels of hemoglobin, hematocrit, erythrocytes, platelets, eosinophils, and lymphocytes. On the dorsum and lateral of the tongue as well as the lower lip mucosa, an intraoral examination revealed erratic white plaques. Oral manifestations are the suspected diagnosis based on the history and clinical presentation. Discussion: HCC patients exhibit an immunodeficiency that leaves them vulnerable to infection. Xerostomia, oral candidiasis, caries, stomatitis ulcers, tooth erosion, and masticatory problems are common oral symptoms. Patients with HCC must have their physical state, disease length and stage, kind of treatment, biological constants, and recommendations from an internal medicine physician taken into account when receiving dental care. Given that topical therapy is the first line of defense against drug interactions, it is advised in this situation. An immunocompromised state brought on by hepatocellular carcinoma leaves the body vulnerable to opportunistic infections like oral candidiasis. Maintaining oral hygiene is a necessary component of the preventative and therapeutic management of candidiasis.